The role of ethnicity in involuntary psychiatric admission in Toronto, Canada in clients presenting with psychosis. Issue 3 (3rd July 2019) - Rotenberg, Martin; Tuck, Andrew; McKenzie, Kwame
ABSTRACT: In the UK, clients from black and minority ethnic groups experience higher rates of involuntary admission. In Canada, despite increasing immigration and diversity, this issue has not been a research focus. This retrospective study examined whether odds of admission, specifically involuntary admission, differed in a sample of 765 clients presenting with psychosis from six different ethnic groups. It was hypothesized that South and East Asian clients would be more likely to be admitted involuntarily. Logistic regression models were constructed from data that is routinely collected on clients who were admitted to hospital. The hypothesis was not supported and ethnicity did not predict admission. Future research should utilize administrative data and focus on equitable access to services in the community.